Management of neonatal difficult airway emergencies in the delivery room. Issue 5 (22nd April 2020) - Lin, Elaina E.; Nelson, Olivia; Isserman, Rebecca S.; Henderson, Alicia A.; Rintoul, Natalie E.; Lioy, Janet; Javia, Luv R.; Tran, Kha M.; Fiadjoe, John E.
Abstract: Neonatal airway emergencies in the delivery room are associated with significant morbidity and mortality. Etiologies vary, but often predispose the neonate to life threatening airway obstruction. With the recent expansion of fetal medicine programs, pediatric anesthesiologists are increasingly being asked to care for these patients. In this review, we discuss common etiologies of difficult airway at delivery, management tools and techniques, and surgical approaches.